The principles of banking - Moorad Choudhry (John Wiley & Sons, 2024)
Hinging on basic principles, this banking handbook omits a lot of product detail and complex mathematics on the more technical aspects of finance and focuses on key issues in bank strategy, liquidity management, management reporting, the yield curve and asset liability management